HUMAN ECOLOGICAL CULTURE AS A BASIS FOR HARMONIOUS DEVELOPMENT OF SOCIETY - Skyba, Оksana (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction.The paper is devoted to the study of the peculiarities of the formation of the ecological culture of man, which is relevant in a modern challenging ecological situation. The aim and tasks. Today the issue of forming ecological culture and ecological consciousness turns out to be one of the most important problems, which is the aim of the study. Research methodology. The theoretical and methodological basis of the study are general and special methods and approaches that will make it possible to trace and take into account important aspects of the development and formation of the ecological culture of mankind. Research results. The global environmental problem of mankind has become the focus of scientists in the late XX and early XXI cc. Scientists have begun to realize the need to change man's attitude to nature and their responsibility for the possible negative consequences of their discoveries, abandoning the areas of activity that can bring disaster. Ecological ethics, which emerged in the last third of the XX c., influenced the formation of new values, and the ecological culture of man, applied a moral status to nature in the system of "man-nature" relations. Thus, humanity is taking the first steps on the road to the idea of a holistic inalienable harmonious existence of man and nature, the spread of moral and ethical principles to nature. Discussion. Today, some scientists fear that advances in the development of science and technology will overshadow humanity's mind and will be accompanied not so much by the creation of new values as by the denial of the cultural heritage of the past. The point is that the achievement of scientific and technological progress is not always good for humanity, because of most of the global problems: environmental, raw materials, and others caused by it. Conclusion. In modern society, it is necessary from childhood to cultivate a caring attitude towards nature, to form the ecological culture of man, and to avoid the consequences of his activities that will negatively affect nature.